Issues in African development : essays in honour of Adebayo Adedeji at 65 - Adedeji, Adebayo; Onimode, Bade.; Synge, Richard (Ibadan : Heinemann Educational Books ; Ijebu-Ode, Nigeria : African Centre for Development and Strategic Studies, 1995)
This book of essays on issues in African Development is a celebration of Professor Adebayo Adedeji's 65th birthday. It is a symbolic microcosm of the tons of goodwill messages from across the globe to this illustrious son of Africa.
Includes index.
Includes bibliographical references: p. 305-321.
rpm 31/08/2016
Loans
Keywords: African cooperation; African development; Africa